2016
DOI: 10.1017/jfm.2016.450
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution velocity measurement in the inner part of turbulent boundary layers over super-hydrophobic surfaces

Abstract: Digital holographic microscopy is used for characterizing the profiles of mean velocity, viscous and Reynolds shear stresses, as well as turbulence level in the inner part of turbulent boundary layers over several super-hydrophobic surfaces (SHSs) with varying roughness/texture characteristics. The friction Reynolds numbers vary from 693 to 4496, and the normalized root mean square values of roughness $(k_{rms}^{+})$ vary from 0.43 to 3.28. The wall shear stress is estimated from the sum of the viscous and Rey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 64 publications
2
67
0
Order By: Relevance
“…The deleterious effect of increasing texture size on the drag observed by these DNS studies is qualitatively consistent with theoretical analysis [28], and experimental investigations [13,15,29].…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…The deleterious effect of increasing texture size on the drag observed by these DNS studies is qualitatively consistent with theoretical analysis [28], and experimental investigations [13,15,29].…”
Section: Introductionsupporting
confidence: 87%
“…Another, texture-related dimensionless parameter is the solid fraction, φ s . A typical range of φ s is 10% − 20% and does not vary by order of magnitude [13][14][15]. In the present study we considered φ s = 1/9, 1/6, and 1/4.…”
Section: B Dimensionless Physical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting k = k * /M a and Γ = Γ * /M a into (5), (14) and (13), with the Henry kinetics (18) and (19), we obtain a set of equations where k and M a have been combined to form k * , thereby reducing by one the number of dimensionless groups. This can be verified by examining the updated version of the complete set of equations (2)- (13), which becomes…”
Section: Problem Description and Governing Equationsmentioning
confidence: 99%
“…Experimental studies have also observed that for sufficiency large roughness size, expressed in wall units, superhydrophobic surfaces resulted in a drag increase rather than a drag decrease. This has been attributed to the protrusion of roughness elements introducing additional drag and roughness-like effects (Bidkar et al 2014;Ling et al 2016;Gose et al 2018). Ling et al (2016) also investigated the effect of increasing the roughness protrusion, for the same texture, by increasing the overlying fluid pressure in their experiments.…”
Section: Introduction and The Drag Reduction Mechanismmentioning
confidence: 99%